Social Capital in the Sustainable Development Tourism: A Case Study of Penyengat Island National Cultural Heritage Area - Surjadi Surjadi; Hartuti Purnaweni; Muh Yusuf; Retno Sunu Astuti (Universitas Teuku Umar, 2022)
Tourism is one of the industries with positive growth and the most dynamic that can make tourism a key sector to encourage economic growth, especially in providing jobs, increasing regional incomes and people's living standards, as well as encouraging the development of other sectors economically. Pulau Penyengat, which is the center of Malay civilization both in language and culture, with a million potentials, as well as characteristics and historical values that support local wisdom and have an important influence on regional economic, social and cultural growth, requires integrated, comprehensive and sustainable effort to become a leading sustainable urban tourism destination. This study aims to explore the role of social capital in supporting the realization of sustainable urban tourism in Pulau Penyengat. The important findings in this research are (1) bounding social capital is a type of social capital that forms and develops in sustainable tourism destinations on Pulau Penyengat; (2) strong ties in the community system are based on values, culture, customs, and kinship relationships; (3) the community is convinced that social capital is the key to success in developing sustainable tourism, although objectively there is a tendency for social capital to fade due to internal and external factors.